The quantification of down-hole fractionation for laser ablation mass spectrometry - J. C. Lloyd; J. C. Lloyd; C. Spandler; S. E. Gilbert; D. Hasterok (Geochronology)
Down-hole fractionation (DHF), a known phenomenon in static spot laser ablation, remains one of the most significant sources of uncertainty for laser-based geochronology. A given DHF pattern is unique to a set of conditions, including material, inter-element analyte pair, laser conditions, and spot geometry. Current modelling methods (simple or multiple linear regression, spline-based regression) for DHF do not readily lend themselves to uncertainty propagation, nor do they allow for quantitative inter-session comparison, let alone inter-laboratory or inter-material comparison.